Circulating metabolites in patients with chronic heart failure are not related to gut leakage or gut dysbiosis - Andraž Nendl; Sajan C. Raju; Peder R. Braadland; Anna Nordborg; Vibeke Bratseth; Kaspar Broch; Silje F. Jørgensen; Pål Aukrust; Karsten Kristiansen; Johannes R. Hov; Marius Trøseid; Ayodeji Awoyemi (PLoS ONE, 2025)
Background The gut microbiota produces numerous metabolites that can enter the circulation and exert effects outside the gut. Several studies have reported altered gut microbiota composition and circulating metabolites in patients with chronic heart failure (HF) compared to healthy controls. Limited data is available on the interplay between dysbiotic features of the gut microbiota and altered circulating metabolites in HF patients. We aimed to examine differences in circulating metabolites between people with and without chronic HF, and their association with gut microbiota dysbiosis and cardiac function. Methods We collected plasma, serum, and stool samples from 123 adult patients with stable chronic HF and left ventricular ejection fraction (LVEF) ≤40%, and healthy controls (plasma: n = 51, stool samples: n = 69). Metabolomic and lipidomic profiling of plasma was performed using liquid chromatography with tandem mass spectrometry. Principal component analysis was used to explore differences in circulating profiles. Over-representation analysis was performed to identify pathways in which relevant metabolites were involved. Stool samples were sequenced using shotgun metagenomics. We calculated a dysbiosis index based on differential abundances of microbial taxa in patients vs. controls. Results After adjusting for age, sex, and sampling location, we identified 67 enriched metabolites and 24 enriched lipids, and 115 depleted metabolites and 6 depleted lipids in HF patients compared to healthy controls. LVEF, N-terminal pro B-type natriuretic peptide, gut leakage markers, dysbiosis index, and fiber intake were not significantly related to any of the differentially abundant metabolites or lipids. Pathways related to energy metabolism differed most between HF patients and controls, however medication adjustment abolished all differences in circulating profiles. Conclusions Patients with chronic HF had distinct metabolomic and lipidomic profiles and energy metabolism differed significantly compared to healthy controls before adjusting for medication use. However, the alterations were not related to gut dysbiosis, gut leakage markers, cardiac function, or fiber intake.